Diabetes, depressive symptoms, and mortality risk in old age: The role of inflammation. Issue 10 (8th May 2019) - Castro‐Costa, Erico; Diniz, Breno S.; Firmo, Josélia O. A.; Peixoto, Sérgio V.; de Loyola Filho, Antônio Ignácio; Lima‐Costa, Maria Fernanda; Blay, Sergio L.
Abstract: Background: Both diabetes and depression increase the mortality risk in the elderly. In this study, we evaluated mortality risk associated with the comorbidity between depression and diabetes. We also assessed the moderating role of inflammation in the mortality risk in this population. Methods: We included a total of 1, 183 community‐dwelling older adults, divided into four groups: "neither diabetes nor depression"; "diabetes only"; "depression only, " and "both diabetes and depression, " and followed‐up for a median of 13.5 years. We evaluated the inflammatory status by the high‐sensitivity C‐reactive protein (hs‐CRP) levels. Date of death was computed by reviewing death certificates. We used Cox's proportional hazards models and additive interactions to evaluate the risk of mortality in the subject groups and the moderating effect of hs‐CRP. Results: Participants with both diabetes and depression had higher death risk (hazard ratio [HR]: 2.33; 95% confidence interval [CI]: 1.59–3.42) than those with each condition alone (HR diabetes: 2.08 95% CI: 1.56–2.76 HR depression: 1.26; 95% CI: 1.03–1.54). High level of hs‐CRP, indicative of high inflammatory status, significantly moderated the risk of mortality in subjects with both diabetes and depression (Bonferroni‐adjusted p = 0.0116). Conclusions: The coexistence of diabetes and depression symptoms is associated with the highest death risk in this population. This risk is moderated by inflammatory status.